Work-family conflict in the public sector: The impact of public service motivation and job crafting - Julia Asseburg (ZBW – Leibniz Information Centre for Economics, 2018)
Public service motivation (PSM) research has recently begun to investigate the “dark sides” of PSM. However, this stream of research is still in its infancy. This study investigates the work-family conflict (WFC) as a potential dark side of PSM and how job crafting, a type of proactive behaviour, mediates this relationship. Using two-wave survey data of 306 civil servants and public employees in Germany, SEM path analyses are conducted. Results suggest that PSM is a strong predictor of WFC and that this relationship is partially mediated by job crafting. In addition, the results suggest that only the demand-based dimensions of job crafting mediate the relationship, whereas the resource-based dimensions do not. Implications for PSM research as well as practical implications are discussed. The study concludes with actionable recommendations for HR managers in the public sector who wish to retain PSM-driven employees.
Keywords: 330; Work-Family Conflict; Public Service Motivation; Job Crafting; Dark sides